Pathogens protection against the action of disinfectants in multispecies biofilms - Sanchez-Vizuete, Pilar; Orgaz, Belen; Aymerich, Stéphane; Le Coq, Dominique; Briandet, Romain (Frontiers in Microbiology, 2015)
Biofilms constitute the prevalent way of life for microorganisms in both natural and man-made environments. Biofilm-dwelling cells display greater tolerance to antimicrobial agents than those that are free-living, and the mechanisms by which this occurs have been investigated extensively using single-strain axenic models. However, there is growing evidence that interspecies interactions may profoundly alter the response of the community to such toxic exposure. In this paper, we propose an overview of the studies dealing with multispecies biofilms resistance to biocides, with particular reference to the protection of pathogenic species by resident surface flora when subjected to disinfectants treatments. The mechanisms involved in such protection include interspecies signaling, interference between biocides molecules and public goods in the matrix or the physiology and genetic plasticity associated with a structural spatial arrangement. After describing these different mechanisms, we will discuss the experimental methods available for their analysis in the context of complex multispecies biofilms.